1987
DOI: 10.1080/00222338708078150
|View full text |Cite
|
Sign up to set email alerts
|

Positive Photoreactive Polyimides. II. Preparation and Characterization of Polyimide Precursors Containing α-(2-Nitrophenyl)ethyl Ester Side Chains

Abstract: The monomers were derived from pyromellitic dianhydride and a42-nitrophenyl)ethanol, which was prepared by selective reduction of 2-nitroacetophenone. Polyimide precursors were synthesized by an interfacial polycondensation technique. Their thermal properties in nitrogen were studied by dynamic thermogravimetry. The photorearrangement of 2-nitrobenzyl ester having a methyl group at the aposition compared to that of the unsubstituted ester was investigated by infrared spectrophotometry. The polymers obtained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Recently, in order to avoid this problem, positive-working photosensitive polyimides that can be developed with water-based solutions have been developed. Kubota et al reported a positive-working photosensitive polyimide precursor prepared from pyromellitic acid di(alpha-(2-nitrobenzyl)ethyl)ester which caused the cleavage of ester linkages [3]. Omote and Yamaoka investigated nifedipine (1,4-dihydro-2,6-dimethyl-4-(nitrophenyl)-3,5pyridinedicarboxylic acid dimethylester) as a dissolution inhibitor in poly(amic acid)s after a post-exposure brake (PEB) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in order to avoid this problem, positive-working photosensitive polyimides that can be developed with water-based solutions have been developed. Kubota et al reported a positive-working photosensitive polyimide precursor prepared from pyromellitic acid di(alpha-(2-nitrobenzyl)ethyl)ester which caused the cleavage of ester linkages [3]. Omote and Yamaoka investigated nifedipine (1,4-dihydro-2,6-dimethyl-4-(nitrophenyl)-3,5pyridinedicarboxylic acid dimethylester) as a dissolution inhibitor in poly(amic acid)s after a post-exposure brake (PEB) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with conventional photoresists, the advantages of PSPIs are not only demonstrated by the outstanding properties of polyimides (PIs), but also by the significant simplification of the pattern formation process. , Although the first commercial PSPIs were of the negative tone type, , the positive tone PSPIs ( p -PSPIs) are more desired on an industrial level. A variety of p -PSPIs have been developed using different chemistries, in which the most popular ones are those composed of a PI precursor, poly­(amic acid) (PAA), and a diazonaphthoquinone photoactive compound (DNQ PAC). In an effort to design PAA–DNQ type p -PSPIs with high contrast imaging, many approaches have been investigated. These approaches can be divided into two aspects: modification of the PAA structures and designing new PACs. No matter which aspect was considered, it is inevitable to understand the interactions between PAA and PACs, and their dissolution inhibitation mechanisms for the design of good p -PSPIs.…”
Section: Introductionmentioning
confidence: 99%
“…Kubota et al reported a positive-working polyimide resist precursor prepared from pyromellitic acid di(alpha-(2nitrobenzyl)ethyl)ester. Cleavage of the ester linkages occurred by the action of UV light [3]. Omote and Yamaoka investigated nifedipine (1,4-dihydro-2,6-dimethyl-4-(nitrophenyl)-3,5-pyridinedicarboxylic acid dimethylester) as a dissolution inhibitor in poly(amic acid)s after a post-exposure bake (PEB) [4].…”
Section: Introductionmentioning
confidence: 99%